Pelatihan Pemulasaran Jenazah Perempuan bagi Kelompok Pemberdayaan dan Kesejahteraan Keluarga - Fauziah, Muna; Azizah, Farkhah; Rozaqti, Herlina; Mungin, Fatkhul (BALE LITERASI, 2024)
The corpse recovery training is a community service program. The program aims to increase knowledge and understanding of the Prasutan Village Family Welfare Development (PKK) group regarding the disposal of women's remains. The corpse recovery training activity was attended by 50 participants who were all female and belonged to the people of Prasutan Village, Ambal District, Kebumen Regency. The method of implementation is through lectures and practices. The stages of implementing activities are the preparation stage, the implementation stage, the mentoring stage, and the evaluation stage. The results of the activity showed the benefit and added understanding to participants in caring for corpses, including bathing, shrouding, and praying. The corpse retrieval training activity was able to motivate the Prasutan Village PKK group to form a corpse retrieval committee for women.